Running from responsibility: athletic governing bodies, corporate sponsors, and the failure to support pregnant and postpartum elite female distance runners - Darroch, F. E.; Giles, A. R.; Hillsburg, H.; McGettigan-Dumas, R. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
This feminist qualitative research draws on data from 14 semi-structured interviews with pregnant or parenting elite female distance runners. Using three theoretical approaches (liberal feminism, radical feminist thought, and strategic essentialism) alongside of thematic analysis, we identified the following themes about elite female distance runners: women do not feel supported by corporate sponsors or athletic governing bodies during pregnancy or postpartum; due to the lack of support, the women plan/strategize pregnancies around competitions, contracts, and spousal support; due to all of the above, the women face stress and uncertainty in their careers that their male counterparts do not. The participants argue that athletic governing bodies and corporate sponsors must be more transparent in their practices and improve policies to create more equitable sporting environments.